2022
DOI: 10.3390/ijms23158759
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Influence of the Selected Range of Visible Light Radiation on the Durability of the Gel with Ascorbic Acid and Its Derivative

Abstract: (1) Background: Depending on the type of hydrophilic polymer used, different types of hydrogels may be chemically stable or may degrade and eventually disintegrate, or dissolve upon exposure to sunlight. Many over-the-counter medications are now stored with a limited control of temperature, humidity and lighting. Therefore, in this study, the photostability of a gel made of cross-linked polyacrylic acid (PA), methylcellulose (MC) and aristoflex (AV) was assessed, and the interaction between the polymers used a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 40 publications
0
6
0
1
Order By: Relevance
“…Some polyols used in cosmetics can extend the half-lives of AA, and the inclusion of glycerin improved the stability of AA in the water-in-oil emulsion more effectively than the inclusion of propylene glycol [ 79 ]. The photooxidation of AA was significantly slower in a gel preparation based on polyacrylic acid and glycerol compared to a single-component solution [ 99 ].…”
Section: Various Approaches To Maximize the Efficacy Of Aamentioning
confidence: 99%
“…Some polyols used in cosmetics can extend the half-lives of AA, and the inclusion of glycerin improved the stability of AA in the water-in-oil emulsion more effectively than the inclusion of propylene glycol [ 79 ]. The photooxidation of AA was significantly slower in a gel preparation based on polyacrylic acid and glycerol compared to a single-component solution [ 99 ].…”
Section: Various Approaches To Maximize the Efficacy Of Aamentioning
confidence: 99%
“…Spectrophotometric methods were simple, accurate, and precise regarding spectral resolution. Moreover, this enhanced sensitivity widens the opportunities for them to be used as stability-indicating methods in quality control. , The FODS method proved suitable for cocrystal quantification, but not limited to, since it can aid in other types of analysis that require quantification of vitamin C, such as currently done for photostability assays of ASC in creams and gels using UV irradiation sources. , …”
Section: Resultsmentioning
confidence: 99%
“…This fact would take place in the HG and the BG but not in the AA system in aqueous solution. According to Golonka et al [ 34 ], the photostability of AA and its derivatives in a hydrophilic environment is related to the substance–polymer interaction. Perhaps, in our formulas, this ionic interaction with the lipid bilayer and ascorbate ion could be related to the ability to stabilize AA that we observe.…”
Section: Resultsmentioning
confidence: 99%
“…The different micro- and nanostructural organizations of both HG and BG, along with the fundamental role of water and lipids in their composition, suggest that they can be a suitable matrix to incorporate AA and protect it from degradation. An improvement in this research, compared to other similar BGs, hydrogels, and encapsulation strategies found in the literature [ 10 , 13 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ], is that our material is composed only of lipids and water. No polymers, resins, acid ascorbic derivatives, or chelating agents (biocompatible or not) are introduced in our formulas.…”
Section: Introductionmentioning
confidence: 92%